Estimation of Throughfall and Stemflow Bacterial Flux in a Subtropical Oak‐Cedar Forest - Thais B. Bittar; Preston Pound; Ansley Whitetree; L. Dean Moore; John T. Van Stan II (Geophysical Research Letters)
Abstract Transport pathways of microbes between ecosystem spheres (atmosphere, phyllosphere, and pedosphere) represent major fluxes in nutrient cycles and have the potential to affect microbially mediated biogeochemical processes. Novel data on bacterial fluxes from the phyllosphere to the pedosphere during rainfall via throughfall (rain dripping from/through the canopy) and stemflow (rain funneled down tree stems) are reported. Bacterial concentrations were quantified using flow cytometry and validated with quantitative polymerase chain reaction assays in rainfall samples from an oak‐cedar forest in coastal Georgia (southeastern U.S.). Bacteria concentrations (cells mL−1) and storm‐normalized fluxes (cells m−2 h−1, cells m−2 mm−1) were greater for cedar versus oak. Total bacterial flux was 1.5 × 1016 cells ha−1 yr−1. These previously unexamined bacterial fluxes are interpreted in the context of major elemental pools and fluxes in forests and could represent inoculum‐level sources of bacteria (if alive), and organic matter and inorganic solute inputs (if lysed) to soils.